Environmental dynamic, business strategy, and financial performance: An empirical study of Indonesian property and real estate industry - Wahyudi, Imam (UI Scholars Hub, 2013)
Firm’s strategic orientation involves synchronizing environmental dynamics, corporate strategy and capital structure in order to achieve firm performance targets. The co-alignment model used successfully in the hospitality industry might be used in a wider context as a framework in explaining these relationships simultaneously. Using the data of public firms in Indonesia during the period of 1996-2010, we found that co-alignment model can be implemented in property and real estate industry as well as in hospitality industry.